In-Silico study of antivirals and non-antivirals for the treatment of SARS-COV-2 - dos Santos, André Flores; Ortiz, Mirkos Martins; Montagner, Giane Engel; Schultz, Julia Vaz; Gomes, Patrícia; Silva, Ivana Zanella da; Fagan, Solange Binotto (Disciplinarum Scientia | Naturais e Tecnológicas, 2022)
In March 2020, it was declared a coronavirus (COVID-19) pandemic disease state by the World Health Organization, which represents a public health concern. Several antiviral and non-antiviral drugs are currently being tested against the COVID-19 disease, some of which have already been approved by health regulatory bodies in some countries. In this study, the objective was to identify the best drugs that are being used to fight the virus through computer simulations in addition to predicting toxicity and antiviral activity. Thus, molecular docking of the compounds arbidol, baricitinib, camostat mesylate, favipiravir, heparin, hydroxychloroquine, molnupiravir, paxlovid, and remdesivir was performed to discover the best points of interaction in the cellular organelles involved in the process of cellular infection by SARS-CoV- 2 and the prediction of toxicology and antiviral activity of the compounds was performed by online computer simulation programs: pkCSM, ProTox-II, GUSAR, ROSC-Pred, and AntiVir-Pred. The best results highlight the drugs heparin as a good protein S blocker, paxlovid as a protease inhibitor, arbidol as a viral entry blocker, baricitinib as an RNA replication inhibitor, and membrane fusion inhibitor. All compounds showed a low risk of toxicity, as most showed antiviral activity. Thus, all compounds, except favipiravir, demonstrated some type of interaction with target cell organelles, but more studies are needed, such as in vitro and in vivo, to obtain reliable results for treatment with small doses of the drug, since the prediction showed small rates of the toxicity, mainly hepatic.